Gestational phthalate exposure and lung function during childhood: A prospective population-based study. (1st November 2022) - Bosch de Basea, Magda; Carsin, Anne-Elie; Abellan, Alicia; Cobo, Inés; Lertxundi, Aitana; Marin, Natalia; Soler-Blasco, Raquel; Ibarluzea, Jesús; Vrijheid, Martine; Sunyer, Jordi; Casas, Maribel; Garcia-Aymerich, Judith
Abstract: The potential effect of gestational exposure to phthalates on the lung function levels during childhood is unclear. Therefore, we examined this association at different ages (from 4 to 11 years) and over the whole childhood. Specifically, we measured 9 phthalate metabolites (MEP, MiBP, MnBP, MCMHP, MBzP, MEHHP, MEOHP, MECPP, MEHP) in the urine of 641 gestating women from the INMA study (Spain) and the forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1 ) and FEV1 /FVC in their offspring at ages 4, 7, 9 and 11. We used linear regression and mixed linear regression with a random intercept for subject to assess the association between phthalates and lung function at each study visit and for the overall childhood, respectively. We also assessed the phthalate metabolites mixture effect on lung function using a Weighted Quantile Sum (WQS) regression. We observed that the phthalate metabolites gestational levels were consistently associated with lower FVC and FEV1 at all ages, both when assessed individually and jointly as a mixture, although most associations were not statistically significant. Of note, a 10% increase in MiBP was related to lower FVC (−0.02 (−0.04, 0)) and FEV1 z-scores (−0.02 (−0.04, −0.01) at age 4. Similar significant reductions in FVC were observed at ages 4 and 7 associated with an increase in MEP and MnBP, respectively, and for FEV1 at age 4 associated with an increase in MBzP. WQS regression consistently identified MBzP as an important contributor to the phthalate mixture effect. We can conclude that the gestational exposure to phthalates was associated with children's lower FVC and FEV1, especially in early childhood, and in a statistically significant manner for MEP, MiBP, MBzP and MnBP. Given the ubiquity of phthalate exposure and its established endocrine disrupting effects in children, our findings support current regulations that limit phthalate exposure. Graphical abstract: Image 1 Highlights: Gestational phthalates exposure was associated with lower lung function at all ages. The lung function decline was stronger in younger than in older children. The reduction in lung function observed at 4 and 7 years was not persistent. MiBP and MBzP were the key phthalate metabolites driving the lung function reduction.